(untitled) (Conferencea, 2022)
Writing skills allow you to communicate clearly with others and create useful resources for the workplace. Even professions that don’t focus on writing require written communication skills, from the initial application to daily tasks and record-keeping. Writing is an activity with many moving parts. A child must bring together vocabulary, grammar and mental processing, and then rely on the physical aspect of handwriting or typing out the words.That’s why it requires ample practice and extensive exposure to language for kids to develop strong writing skills.And because young learners can’t just sit down and write the perfect draft, they need to learn the art of revision too.